Emotion in Interaction 2012
DOI: 10.1093/acprof:oso/9780199730735.003.0006
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Affiliation in the Reception of Conversational Complaint Stories

Abstract: This chapter investigates the linguistic resources deployed by recipients of conversational complaint stories to show affiliation (or not) with the teller, affiliation being understood as the display of support and endorsement for a conveyed affective stance, here typically anger and/or indignation. Among the verbal means for affiliative reception are claims of understanding, congruent negative assessments and by-proxy justifications, while factual follow-up questions, minimal responses and withholdings are sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(81 citation statements)
references
References 21 publications
(13 reference statements)
4
72
1
4
Order By: Relevance
“…Immediacy in responding is typical of affiliative responses, whereas disaffiliative ones are often delayed (Couper-Kuhlen, 2012). If the target of speech and language therapy is to encourage and improve the client's communication, it may not be useful to affiliate with the frustrated emotional stance.…”
Section: A Trajectory From Struggling To Shared Laughtermentioning
confidence: 99%
“…Immediacy in responding is typical of affiliative responses, whereas disaffiliative ones are often delayed (Couper-Kuhlen, 2012). If the target of speech and language therapy is to encourage and improve the client's communication, it may not be useful to affiliate with the frustrated emotional stance.…”
Section: A Trajectory From Struggling To Shared Laughtermentioning
confidence: 99%
“…Specific findings include synchrony in body movement (Ramseyer & Tschacher, 2011), vocal prosody (e.g., pitch, intonation, accent, rhythm and loudness, use of pauses; Couper-Kuhlen, 2012; Weiste & Peräkylä, 2013, 2014), as well as physiological synchrony such as changes in skin-conductance (Marci et al, 2007; see also early studies on heart-rate, Di Mascio, 1955; and emotional reactivity, Lacey, 1959). In general, these studies have shown that greater synchrony is correlated with better ratings of therapist empathy and other measures of the therapeutic relationship, and treatment outcome (see Reich et al, 2014 for an exception).…”
Section: Introductionmentioning
confidence: 99%
“…Research in this field has started to specify the role of prosodic resources in expressing emotion in naturally occurring spoken interaction (see Peräkylä & Sorjonen, 2012). Some studies, using everyday 688 E. Weiste and A. Peräkylä conversations as data, have systematically investigated the prosodic design of empathic utterances (see e.g., Couper-Kuhlen, 2012;Selting, 1994; see also Heritage, 2011, for empathic moments in interaction). Most recently, Couper-Kuhlen (2012) explored verbal and prosodic means of conveying empathy in response to the display of anger and indignation in everyday complaint stories.…”
Section: Introductionmentioning
confidence: 99%